THE EFFECT OF ADDING MAGGOT FLOUR BLACK SOLDIER FLY ON PERFORMANCE AND PROFILE OF WHITE BLOOD BROILER - Pandie, Viniesa; Datta, Frans Umbu; Simarmata, Yohanes Timbun Raja Mangihut Ronael (Buletin Veteriner Udayana, 2023)
Broiler chickens are superior breeds resulting from crossbreeding and genetic engineering that have high productivity, especially meat production, and can be harvested at the age of 5 weeks. Broiler chicken productivity can be seen from the performance and white blood cell profile through the feed consumed. One of them is BSF maggot flour. The purpose of this study was to see whether the addition of BSF maggot flour affected ration consumption, feed conversion, body weight gain, and white blood cell profile in starter phase broiler chickens. The method used is an experimental method, using a completely randomized design (CRD). 100 chickens used were divided into 4 treatments (P0, P1, P2, P3) with 25 in each treatment. Analysis of the data used is the Analysis of Variance with the results of the analysis presented in the form of tables and curves. Based on the results obtained statistically that BSF (Black Soldier Fly) maggot flour had no significant effect on body weight gain, ration consumption and feed conversion. From the results of blood tests, BSF maggot flour (Black Soldier Fly) has an effect on the differential of white blood cells, but it has no significant effect because the results of the examination obtained various results influenced by various things such as environmental conditions, weather and climate, and nutrition. Suggestions for further research are to determine the digestibility of the feed added to BSF (Black Soldier Fly) maggot flour and to perform a proximate analysis on the BSF (Black Soldier Fly) maggot flour to be used.